Relationships of Walking and non-Walking Physical Activities in Daily Life with Cognitive Function and Physical Characteristics in Male Patients with Mild Chronic Obstructive Pulmonary Disease. Issue 16 (December 2022) - Egoshi, Shojiro; Horie, Jun; Nakagawa, Akinori; Matsunaga, Yuriko; Hayashi, Shinichiro
BACKGROUND: Chronic obstructive pulmonary disease (COPD) is accompanied by dyspnea on exertion due to airflow limitation caused by bronchial stenosis, with afflicted patients being less physically active. Therefore, physical activity is important for disease management. OBJECTIVES: This study aimed to examine the relationships of walking and non-walking physical activities with cognitive function or physical characteristics of patients with mild COPD in a community without respiratory rehabilitation. DESIGN: Cross-sectional study. DATA SOURCES AND METHODS: We included 40 male patients (mean age, 75.7 ± 6.7 years) with stable mild COPD. A three-axis accelerometer was used to evaluate walking and non-walking physical activities in daily life. Cognition, respiratory function, skeletal muscle mass, limb muscle strength, exercise capacity, and health-related quality of life were assessed. RESULTS: Regarding daily exercise amount (metabolic equivalents × hours; Ex), 87.5% of the participants had walking activities of 0–2 Ex, while 67.5% had non-walking activities of 1–3 Ex. Walking activity was significantly correlated with cognitive function ( P < .05), walking distance ( P < .01), and health-related quality of life ( P < .05), but not with muscle mass. However, non-walking activity was significantly correlated with the body mass index ( P < .05), muscle mass ( P < .05), and walking distance ( P < .01), but not with cognitive function. Moreover, the relationship between non-walking activity and health-related quality of life was weaker than the corresponding relationship with walking activity. CONCLUSION: In patients with mild COPD, walking and non-walking physical activities showed different relationships with cognitive function and physical characteristics. The findings suggest that self-management of such patients requires maintenance of both walking and non-walking activities in a balanced manner.